Local Wisdom, Environmental Management and Sustainable Traditions in Naga Village, Tasikmalaya Regency - Ratnasari, Dewi; Sidiq, Fahmi; Saputra, Jumadil (International Journal of Ethno-Sciences and Education Research, 2023)
Kampung Naga, a traditional village in Tasikmalaya Regency, West Java, Indonesia, shows a real example of how local wisdom and sustainable environmental management can become the foundation of community life. This article describes settlement patterns, local wisdom values, and taboo practices and customary laws in Kampung Naga. Regular community settlement patterns, use of traditional technology, and awareness of the importance of protecting the environment are the core of their environmental sustainability. Values such as discipline, honesty, and mutual cooperation, as well as respect for tradition, form the basis of community life. Taboos and customary laws play a role in maintaining cultural values and maintaining peace in the community. Kampung Naga's success in maintaining their traditions and environment is an inspiration for the modern world which often faces sustainability challenges.